(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Men need to adopt a cooperative work ethic if they are ever going to really understand the heavyload of various responsibilities put on women. Moreover, if managers want their subordinate women toenjoy their occupations, they must have an ethical approach towards them. Instead of feeling bad aboutthemselves because they didn’t do enough to help their kids grow up, working women should learn tomanage their time and priorities so that they don’t have to choose between their careers and their families.The purpose of this work is to investigate how a mother’s environment might influence her child’smaturation.